2016
DOI: 10.1080/21645515.2015.1132964
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with adults' perceived need to vaccinate against hepatitis B in rural China

Abstract: Hepatitis B virus (HBV) infection is a serious public-health issue in China. While the hepatitis B vaccine is effective in preventing HBV infection, the HBV vaccination coverage rates among Chinese adults remain low. From a survey of rural adults from 7 provinces in China, we identified a unique HBV at-risk group: rural adults who had no history of HBV vaccination and had no plan to HBV vaccinate in the future. We divided this 'no history-no plan' group into those who identified No-need to vaccinate and those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…In this study, we found that women with lower levels of education had high rate of willingness to vaccinate, but this association was not statistically significant when being adjusted in regression model. Previous studies in China were in line with us when it was found that education was negatively correlated with the need of HBV vaccine and willingness to pay for it [16, 22]. The reason of this phenomenon is unclear.…”
Section: Discussionsupporting
confidence: 54%
“…In this study, we found that women with lower levels of education had high rate of willingness to vaccinate, but this association was not statistically significant when being adjusted in regression model. Previous studies in China were in line with us when it was found that education was negatively correlated with the need of HBV vaccine and willingness to pay for it [16, 22]. The reason of this phenomenon is unclear.…”
Section: Discussionsupporting
confidence: 54%
“…Logistic regression was used to assess the association between the outcome variable (vaccine uptake) and the independent variables (sociodemographics, knowledge, and risk perception regarding hepatitis B infection). First, all independent variables that had an association with the outcome variable based on previous studies [ 12 , 15 , 23 , 24 , 25 , 26 , 27 , 28 ] were included into a univariable logistic regression model, and crude odds ratios (COR) were obtained (model 1, Table 1 ). Subsequently, a multivariable logistic regression was applied to calculate mutually adjusted odds ratios (AOR) (model 2, Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that the intention to receive the HBV vaccine is affected by individual's knowledge of HBV and the HB vaccine [11 12]. Research showed that migrant workers have poorer cognition of HBV and the HB vaccine, and a higher HBV prevalence rate, than permanent workers due to their poorer education and health awareness levels, living in groups and lower accessibility to health care [13][14][15][16]. Previous Chinese studies have also identified an individual's knowledge and cognition of HB and the HB vaccine as key factors explaining HB vaccination behavior, but these studies only employed partial measures of HBV cognition [17][18][19].…”
Section: Introductionmentioning
confidence: 99%